Why Political Appointments to Truth Commissions Cause Difficulties for these Institutions: Using the Crisis in the Transitional Justice Process in Nepal to Understand How Matters of Legitimacy and Credibility Undermine Such Commissions. (8th May 2020) - Sarkin, Jeremy; Bhandari, Ram Kumar
Abstract: Over five decades and with dozens of examples of truth commissions to look back on, an undeniable aspect of their legacy is that the world has become far more focused on dealing with the past and uncovering the truth about past atrocities. While there is typically a focus in the literature on the more widely publicized and famous truth commissions, scores of other processes have taken place, especially since the 1990s. Post-conflict or divided societies have designed institutions in ways that achieve specific objectives but at the same time conform to international standards, creating a reputation of being both democratic and accountable. Using the prism of Nepal, this article examines why the process to establish transitional justice mechanisms, and specifically truth commissions, needs to be legitimate and credible for them to be effective and be impactful. It specifically examines issues relating to appointments to such institutions and why such appointments need to be done independently and not overtly politically. It scrutinizes why appointment mechanisms and processes are so important to enhancing the legitimacy and independence of such bodies. The case of Nepal is used as an example to extrapolate conclusions about the problems that affected its processes, and the various crises that have emerged in those processes. The article argues that commissioners ought to be chosen on the basis of their impartiality, moral integrity, and known commitment to human rights and disclosure of the truth. This is essential to ensure that the process is seen to be independent and credible.